Evaluation of Ursodeoxycholic Acid Bioavailability from Immediate- and Sustained-release Preparations Using Gas Chromatography-Mass Spectrometry and High-performance Liquid Chromatography - Scaliaa, Santo; Scagliarinib, Raffaella; Pazzib, Paolo (Arzneimittelforschung, 2000)
An improved procedure is presented for the determination of ursodeoxycholic acid (CAS 128-13-2, UDCA) in human plasma and bile after oral administration of UDCA-containing dosage forms. The plasma samples after solid-phase extraction with silica-based C18- and strong anion exchange cartridges were assayed by gas chromatography-mass spectrometry (GC-MS) using selected-ion monitoring. The hexafluoroisopropyl trifluoroacetate ester derivative of UDCA was selected for GC analysis since it is easily and rapidly prepared by a one-step reaction. Biliary UDCA levels were determined by a rapid and simple high-performance liquid chromatographic (HPLC) method with on-line sample purification. This analytical protocol was used to investigate the pharmacokinetic of a new sustained-release capsule of UDCA in comparison with a reference immediate-release preparation after single oral administration. Statistical evaluation of the area under the plasma concentration-time curves indicated that two formulations are equivalent with regard to the amount of drug absorbed. However, pharmacokinetic data showed that with the sustained-release preparation a significantly delayed mean peak plasma level was reached compared with the reference preparation. Moreover, the immediate- and extended-release capsules were found to achieve a comparable degree of biliary enrichment with UDCA.
Keywords: CAS 128-13-2; Ursodeoxycholic acid, Bioavailability, sustained-release capsule